2013
DOI: 10.1186/1556-276x-8-448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on heat capacity of nanofluids based on molten salts as PCM for thermal energy storage

Abstract: In this study, different nanofluids with phase change behavior were developed by mixing a molten salt base fluid (selected as phase change material) with nanoparticles using the direct-synthesis method. The thermal properties of the nanofluids obtained were investigated. These nanofluids can be used in concentrating solar plants with a reduction of storage material if an improvement in the specific heat is achieved. The base salt mixture was a NaNO3-KNO3 (60:40 ratio) binary salt. The nanoparticles used were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(144 citation statements)
references
References 53 publications
8
135
1
Order By: Relevance
“…to the DSC measurements and the SEM images, it may be concluded that the homogeneous dispersion of the nanoparticles favorably influences the specific heat enhancement of the nanofluids. Regarding the enhanced specific heat of molten salt nanofluids, the higher heat capacity of the nanoparticles, the interfacial thermal resistance at the solid-liquid interface, and the formation of the compressed liquid layer near the nanoparticles were proposed as mechanisms contributing to the increase of the specific heat [19,23,45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…to the DSC measurements and the SEM images, it may be concluded that the homogeneous dispersion of the nanoparticles favorably influences the specific heat enhancement of the nanofluids. Regarding the enhanced specific heat of molten salt nanofluids, the higher heat capacity of the nanoparticles, the interfacial thermal resistance at the solid-liquid interface, and the formation of the compressed liquid layer near the nanoparticles were proposed as mechanisms contributing to the increase of the specific heat [19,23,45].…”
Section: Resultsmentioning
confidence: 99%
“…Needleshaped structures and network-like structures are often shown in research papers concerning the specific heat of molten salt nanofluids [23,45]. It is reasonable to consider that the special structures are relevant to the specific heat increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About the latent heat enhancement, there is lack of information. However, some studies performed by University of Perugia reported an increase of 15% mainly with silica-alumina nanoparticles in nitrate mixture [22] and also in KNO 3 as molten salt having a melting point of 334°C (the latent heat increased by 12%). In both studies, the NEPCMs were produced in water solution [23].…”
Section: Heat Storage Materialsmentioning
confidence: 98%
“…Therefore, thermal engineering is needed in process of mixing nanoparticles into PCM without reducing heat capacity of PCM. Mixing nanoparticle with PCM has been conducted by many researchers to increase latent heat [8,9] and heat capacity [10].…”
Section: Introductionmentioning
confidence: 99%